HYDRODYNAMICS MODELING OF CISADANE COASTAL RESERVOIR - Caesar Adine Mackbon, Mikha-El
Jakarta are one the major cities in the the world that cannot escape from sinking cities phenomenon that caused by sea level rise. In addition to rising sea levels caused by global warming and climate change. The sinking of coastal cities is also caused by land subsidence caused by excessive groundwater extraction which is directly related to the rate of urbanization and increasing population in coastal areas. Various efforts such as the construction of sea dikes and appeals for groundwater extraction have been made to overcome the sinking of Jakarta but have not addressed the existing problems. Coastal reservoirs are a solution offered to overcome the problem of rising sea levels and also land subsidence due to groundwater extraction. This final assignement will simulate flows due to tides using Delft3D-FLOW which will be carried out in the Cisadane river estuary area. The model will be created using the help of Delft Dashboard to create grids, bathymetry of waters, and boundary conditions. Then, a simulation will be carried out by varying the value of the Manning and Chezy roughness coefficients. The results of the model simulation will be validated with environmental data, such as water level elevation due to tides and current velocity due to tides. The validation method is carried out by calculating the error from the modeling result value with environmental data. A reliable model will generate a small difference with events in the field, therefore the error method chosen for validation is the error difference method. This difference value will be compared to the range of measurement data. The model is reliable if the resulting error value is less than 10% for water level elevation and less than 20% for current velocity. After the model is valid and can be said to be reliable, the model is expected to be a reference in the design of the Cisadane coastal reservoir.